Healthy life expectancy vs health expenditure by sullivan method in Malaysia - Muhammad Hakeem Omar; Nurin Haniah Asmuni; Sharifah Nazatul Shima (Institute of Advanced Engineering and Science, 2019)
The improvement of mortality rates in many countries over the world has a major impact on cost associated with living longer due to mortality and morbidity risk. In particular, the trend in life expectancy of Malaysian population has steadily increased for many years where in 2017, Malaysian are expected to live up to 74.8 years compared to 74.3 years in 2011. Life expectancy can be defined as the average period of a person may expect to live, while the definition of disability-free life expectancy is the average number of years a person is expected to live without health disability. If a person takes a good care and services through the advancement of medical technology, it may expend the period of life expectancy for a person. Thus, longevity may have a positive relationship with health expenditure. United State for instance spends more on health across years, however United State becomes the outlier as compared to other countries with higher percentage of increase in life expectancy per dollar spent on health expenditure. Disability or disability-free life expectancy can rise at certain degree among Malaysian. The general public do not know whether longevity will expose a person to a greater period spend in disability state or not. Therefore, this paper presents healthy life expectancy vs. health expenditure by Sullivan method in Malaysia to provide further understanding of morbidity rate for Malaysian population due to longevity. This paper calculates the disability-free life expectancy for Malaysian population which then will be used in country comparison. Relationship between disability-free life expectancy and health expenditure will be studied. Sullivan method will be applied in the calculation by using a period life table based on age and gender groups.